2018
DOI: 10.1111/1750-3841.14285
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic Effects of Capsaicinoids and Lactobacillus plantarum Swun5815 Combined by Inhibiting Cholesterol Synthesis and Increasing Bile Acid and Sterols Excretion on Ovariectomized Rats

Abstract: This study evaluated the hypocholesterolemic effects and potential metabolism of single and combined administrations of capsaicinoids and Lactobacillus plantarum SWUN5815 in ovariectomized rats. Forty female Sprague-Dawley rats were divided into 5 treatment groups. One group was sham-operated (with 1 mL/100 g BW physiological saline), and the 4 other groups were double-ovariectomized: OVX-CON (with 1 mL/100 g BW physiological saline), OVX-CAP (with 1 mL/100 g BW physiological saline and fed with food containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…[ 15 ] Paquette proved that fatty acid oxidation decreased in the liver of OVX rats; [ 16 ] additionally, increased food intake may be another reason for the increase in fatty tissue in OVX rats, although some research has indicated that there is no significant alteration in food intake, but that instead, fatty acid metabolism is slower in OVX rats. [ 17,18 ] Consequently, the specific reason why Glycine alleviated weight gain needs to be further explored in future. Traditional estrogen therapy may raise the risk of breast cancer and cardiovascular disease, [ 19 ] so it is necessary to evaluate any estrogen‐like effect of glycine.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Paquette proved that fatty acid oxidation decreased in the liver of OVX rats; [ 16 ] additionally, increased food intake may be another reason for the increase in fatty tissue in OVX rats, although some research has indicated that there is no significant alteration in food intake, but that instead, fatty acid metabolism is slower in OVX rats. [ 17,18 ] Consequently, the specific reason why Glycine alleviated weight gain needs to be further explored in future. Traditional estrogen therapy may raise the risk of breast cancer and cardiovascular disease, [ 19 ] so it is necessary to evaluate any estrogen‐like effect of glycine.…”
Section: Discussionmentioning
confidence: 99%
“…In other ovariectomy-induced osteoporosis studies, body weight gains were observed to occur without any effect on the appetite (Banin et al 2017;Ren et al 2018). Obesity is one of many symptoms that women face during the menopausal transition due to lack of oestrogen, which results in increased body weight (Choi et al 2017).…”
Section: Effect Of L Plantarum B719 Fmp On the Growth Performance Ofmentioning
confidence: 95%
“…136 Regarding the mechanism of cholesterol lowering by probiotics, it has been found that Lactobacillus plantarum Swun5815 can influence cholesterol metabolism in ovariectomized rats by inhibiting cholesterol synthesis and promoting bile acid excretion. 137 Although the liver is the primary producer of cholesterol, the relationship between cholesterol and sex steroid hormones remains within target organs such as the ovary. Further research is needed to elucidate how cholesterol production in the liver affects ovarian sex hormone secretion at the source (Fig.…”
Section: Cholesterolmentioning
confidence: 99%